Comparative study of biodiesel, GTL fuel and their blends in context of engine performance and exhaust emission - Sajjad, H.; Masjuki, Haji Hassan; Varman, Mahendra; Khan, Mohammad Mahmudur Rahman; Arbab, M.I.; Imtenan, S.; Sanjid, A. (Elsevier, 2014)
Abstract Crude oil price hikes, energy security concerns and environmental drivers have turned the focus on alternative fuels. Gas to liquid fuel (GTL) derived from Fisher-Tropsch synthesis, is regarded as a promising alternative diesel fuel, considering the adeptness to use directly as a diesel fuel or in blends with petroleum-derived diesel in CI engines. GTL has distinctly different characteristics than fossil diesel fuel due to its paraffinic nature, virtually zero sulphur, low aromatic contents and very high cetane number. In this study, an unmodified single cylinder 4 âstroke diesel engine was used to investigate diesel, GTL fuel and their blends in terms of engine performance and exhaust emission characteristics. GTL and its blends demonstrated improved engine performance increasing maximum power 9.1, brake thermal efficiency 20 and lowering BSFC 9.1 than diesel. Exhaust emissions also showed diminutions in CO (22â¼25), HC (30â¼40) and NO (6â¼8). These improvements ensure the potential for the application of GTL diesel blends.